Question
Asked Sep 23, 2019
3 views

Given G(t) = 8 − 6t, write  G(−4 + h) − G(−4) in simplest form.

check_circle

Expert Answer

Step 1

Consider the given function G(t) = 8 – 6t.

First compute G(–4 + h) as follows.

G(-4 h)864 h)
-824 6h
-32-6h
help_outline

Image Transcriptionclose

G(-4 h)864 h) -824 6h -32-6h

fullscreen
Step 2

Similarly, compute G(–4).

=8 - 6
G(-4) 8-6(-4)
=824
- 32
help_outline

Image Transcriptionclose

=8 - 6 G(-4) 8-6(-4) =824 - 32

fullscreen
Step 3

Now simplify the expres...

G(-4 )G() = 32-6h-32
=6h
help_outline

Image Transcriptionclose

G(-4 )G() = 32-6h-32 =6h

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra